Metal Mirrors of the Volga Bolgaria and the Bolgar Region of the Golden Horde as an Intercultural Phenomenon - Rudenko Konstantin A. (Поволжская археология, 2025)
The article deals with the metal mirrors, found in the Volga Bolgaria and the Bolgar region of the Golden Horde. They are kept in the funds of Tatarstan museums and personal collections. 778 pieces of metal mirrors have been studied. Some of them have been preserved fully, some of the artifacts are in the form of fragments. All of them are made of non-ferrous metal alloy. The author in his study relied on the classification of medieval metal mirrors, developed by G.A. Fedorov-Davydov, with additions based on the subjects of the images on the mirrors. The groups into which mirrors are combined according to this principle are indicated by letters of the Russian alphabet. The systematization of these artifacts showed that mirrors with images of two fishes, tulips, and the so-called “wise men” were used most often by the population of the region under consideration. All of these products have different cultural origins: China, the Far East, Iran. Nevertheless, these plots were organically included in the Bolgar mental space. The author claims that their widespread during the Golden Horde period is not associated with the Muslim tradition. They were based on the traditional use of metal mirrors by nomads who were on the territory of Volga Bolgaria in pre-Mongol times and made up a significant part of the population of the Bolgar region during the Golden Horde period. Also, there is a very unlikely that metal mirrors, except for the replication of a small number of popular types, were made in Bulgar. Most of them were imported, including fragments of mirrors.